AltitudeOmics: exercise‐induced supraspinal fatigue is attenuated in healthy humans after acclimatization to high altitude. (April 2014) - Goodall, S.; Twomey, R.; Amann, M.; Ross, E. Z.; Lovering, A. T.; Romer, L. M.; Subudhi, A. W.; Roach, R. C.
Abstract Aims We asked whether acclimatization to chronic hypoxia (CH) attenuates the level of supraspinal fatigue that is observed after locomotor exercise in acute hypoxia (AH). Methods Seven recreationally active participants performed identical bouts of constant‐load cycling (131 ± 39 W, 10.1 ± 1.4 min) on three occasions: (i) in normoxia (N, PIO2, 147.1 mmHg); (ii) in AH (FIO2, 0.105; PIO2, 73.8 mmHg); and (iii) after 14 days in CH (5260 m; PIO2, 75.7 mmHg). Throughout trials, prefrontal‐cortex tissue oxygenation and middle cerebral artery blood velocity (MCAV) were assessed using near‐infrared‐spectroscopy and transcranial Doppler sonography. Pre‐ and post‐exercise twitch responses to femoral nerve stimulation and transcranial magnetic stimulation were obtained to assess neuromuscular and corticospinal function. Results In AH, prefrontal oxygenation declined at rest (Δ7 ± 5%) and end‐exercise (Δ26 ± 13%) (P < 0.01); the degree of deoxygenation in AH was greater than N and CH (P < 0.05). The cerebral O2 delivery index (MCAV × CaO2) was 19 ± 14% lower during the final minute of exercise in AH compared to N (P = 0.013) and 20 ± 12% lower compared to CH (P = 0.040). Maximum voluntary and potentiated twitch force were decreased below baseline after exercise in AH and CH, but not N. Cortical voluntary activation decreased below baseline after exercise in AH (Δ11%, P = 0.014), but not CH (Δ6%, P = 0.174) or N (Δ4%, P = 0.298). A twofold greater increase in motor‐evoked potential amplitude was evident after exercise in CH compared to AH and N. Conclusion These data indicate that exacerbated supraspinal fatigue after exercise in AH is attenuated after 14 days of acclimatization to altitude. The reduced development of supraspinal fatigue in CH may have been attributable to increased corticospinal excitability, consequent to an increased cerebral O2 delivery.